SOLVING THE INVERSE PROBLEM IN DIRECT CURRENT PROFILING METHODS IN A LINEAR FORMULATION - Aleksandrov, P.N.; Krizsky, V.N. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
Profiling methods are used to study the physical properties of the geological environment in the horizontal direction, as a rule, of large geological objects in length or area, when the measuring installation moves along a given trajectory (profile) by means of a carrier. A feature of the profiling method is the fixation of the distance, mainly between sources and receivers, when moving the entire installation along the profile. The determination of the physical properties of a geological object is based on solving the inverse coefficient problem of mathematical physics. The paper proposes a new approach to solving inverse coefficient problems based on data measured by profiling installations in the direct current electrical exploration method, and based on linear volumetric integral equations. Examples of numerical implementation of the solution of the inverse profiling problem in three-dimensional inhomogeneous anisotropic models of the geological environment are considered.